Planning Of Islamic Religious Education With A Scientific Approach In SD Negeri 1 Mentawa - Muspian; Aslan; Kamil (IJGIE (International Journal of Graduate of Islamic Education), 2022)
The learning process of Islamic Religious Education uses a scientific approach that is carried out includes three domains, namely: attitudes (affective), knowledge (cognitive), and skills (psychomotor). Innovative and effective through the realm of attitudes, knowledge, and skills that are interconnected. The learning process of Islamic Religious Education at SDN 1 Mentawa uses a scientific approach where every activity needs a good plan if the goals are to be achieved. Educators need to make a PAI learning plan with a scientific approach; educators prepare planning tools such as porta, promissory notes, syllabus, lesson plans, learning methods, media, and evaluation.